From Ergolines to Indoles: Improved Inhibitors of the Human H3 Receptor for the Treatment of Narcolepsy. Issue 2 (12th November 2014) - Auberson, Yves P.; Troxler, Thomas; Zhang, Xuechun; Yang, Charles R.; Feuerbach, Dominik; Liu, Yu‐Chih; Lagu, Bharat; Perrone, Mark; Lei, Lijun; Shen, Xiaoxia; Zhang, Dushan; Wang, Chunxiu; et al.
Abstract Ergolines were recently identified as a novel class of H3 receptor (H3R) inverse agonists. Although their optimization led to drug candidates with encouraging properties for the treatment of narcolepsy, brain penetration remained low. To overcome this issue, ergoline 1 ((6aR, 9R, 10aR)‐4‐(2‐(dimethylamino)ethyl)‐N‐phenyl‐9‐(pyrrolidine‐1‐carbonyl)‐6, 6a, 8, 9, 10, 10a‐hexahydroindolo[4, 3‐fg]quinoline‐7(4H)‐carboxamide)) was transformed into a series of indole derivatives with high H3R affinity. These new molecules were profiled by simultaneous determination of their brain receptor occupancy (RO) levels and pharmacodynamic (PD) effects in mice. These efforts culminated in the discovery of 15 m ((R)‐1‐isopropyl‐5‐(1‐(2‐(2‐methylpyrrolidin‐1‐yl)ethyl)‐1H‐indol‐4‐yl)pyridin‐2(1H)‐one), which has an ideal profile showing a strong correlation of PD effects with RO, and no measurable safety liabilities. Its desirably short duration of action was confirmed by electroencephalography (EEG) measurements in rats.